Impact of Chlorogenic Acid on Peripheral Blood Mononuclear Cell Proliferation, Oxidative Stress, and Inflammatory Responses in Racehorses during Exercise - Izabela Dąbrowska; Jowita Grzędzicka; Adrianna Niedzielska; Olga Witkowska-Piłaszewicz (Antioxidants, 2023)
Green coffee extract is currently of great interest to researchers due to its high concentration of chlorogenic acid (CGA) and its potential health benefits. CGA constitutes 6 to 10% of the dry weight of the extract and, due to its anti-inflammatory properties, is a promising natural supplement and agent with therapeutic applications. The purpose of our study was to discover the effects of CGA on peripheral blood mononuclear cell proliferation, and the production of pro- and anti-inflammatory cytokines as well as reactive oxidative species (ROS) in horses during exercise. According to the findings, CGA can affect the proliferation of T helper cells. In addition, at a dose of 50 g/mL, CGA increased the activation of CD4+FoxP3+ and CD8+FoxP3+ regulatory cells. Physical activity decreases ROS production in CD5+ monocytes, but this effect depends on the concentration of CGA, and the effect of exercise on oxidative stress was lower in CD14+ than in CD5+ cells. Regardless of CGA content, CGA significantly increased the release of the anti-inflammatory cytokine IL-10. Moreover, the production of IL-17 was greater in cells treated with 50 g/mL of CGA from beginners compared to the control and advanced groups of horses. Our findings suggest that CGA may have immune-enhancing properties. This opens new avenues of research into the mechanisms of action of CGA and possible applications in prevention and health promotion in sport animals.